IMPROVEMENT OF SELF EFFICACY AND STUDENT LEARNING OUTCOMES USING ARGUMENT DRIVEN INQUIRY LEARNING MODEL - Choirun Nikmah; Tukiran Tukiran; Harun Nasrudin (Pendidikan Kimia Unimus, 2020)
This research aimed to to improve self efficacy and student learning outcomes on electrolyte and non electrolyte and non-electrolyte material using Argument Driven Inquiry (ADI) learning model. The test was applied to the 34 students of grade X-6 in Senior high school 7 of Surabaya. Development model of this teaching method used the three stages 4D model from Thiagarajan (define, design, develop). The application stage in the class used pre-experimental, pretest – posttest design. The evaluation used the self efficacy questionnaire, motivation questionnaire and pretest –posttest problems. The result found that the increase of average students’ self efficacy was 0.6 and the average increase of motivation was 0.6. In other way, the average increase of learning result was 0.7 in high category. Based on the data analysis using ADI learning model can improve self efficacy and student learning outcomes.